The Potential Value of Gastric Histopathology for Predicting Colorectal Adenomatous Polyps Among the Chinese Population: A Retrospective Cross-Sectional Study - Li, Weiwei; Zhang, Lin; Jing, Yuanming; Yang, Yanfei; Wang, Yulong (Frontiers in Oncology, 2022)
Background: It remains unknown whether gastric histopathology is associated with the occurrence of colonic neoplasms. We aimed to clarify the correlation between gastric histopathology and different types of colorectal polyps (CP) and colorectal cancer (CRC), and whether various gastric histopathologies are risk factors for different types of CP and CRC. Methods: A retrospective cross-sectional study was conducted on 5,986 patients who underwent gastroscopy and colonoscopy simultaneously at Shaoxing People’s Hospital from August 1, 2019, to May 31, 2020. The Pearson χ2 test was used to analyze the occurrence of various gastric histopathologies in different types of CP and CRC, and logistic regression was used to determine whether various gastric histopathologies were risk factors for different types of CP and CRC. Results: For Chinese population, male sex (odds ratio [OR] 1.67, 95% confidence interval [CI] 1.41–1.97, P<0.001) and old age (OR 1.03, 95% CI 1.02–1.04, P<0.001) were risk factors for non-adenomatous polyps (NAP), but Helicobacter pylori (H. pylori) and various gastric histopathologies were not significant in the NAP compared with the normal group. Nevertheless, it is noteworthy that, similar to male sex and old age, H. pylori (OR 1.22, 95% CI 1.08–1.38, P=0.002), low-grade intraepithelial neoplasia (LGIN) (OR 1.79, 95% CI 1.21–2.66, P=0.004), gastric fundus gland polyps (FGPs) (OR 1.44, 95% CI 1.11–1.87, P=0.007), hyperplastic/inflammatory gastric polyps (GHP or GIP) (OR 1.50, 95% CI 1.06–2.12, P=0.022) and atrophy/intestinal metaplasia (AG or IM) (OR 1.27, 95% CI 1.13–1.43, P<0.001) were all risk factors for colorectal adenomatous polyps (AP). However, the results of CRC showed that old age (OR 1.13, 95% CI 1.10–1.16, P<0.001) and H. pylori (OR 1.67, 95% CI 0.99–2.75, P<0.05) were risk factors for CRC (OR 1.67, 95% CI 0.99–2.75, P<0.05), but not sex and various gastric histopathologies (P>0.05). Conclusion: Gastric histopathology, such as AG or IM, LGIN, FGP, and GHP or GIP, were risk factors for AP, but not for NAP and CRC, indicating that gastric histopathology has potential predictive value for AP in the Chinese population.